ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN KONVENSIONAL DAN PERBANKAN SYARIAH - Maria Euphrasia Dandung; Paulina Yuritha Amtiran; Marselina Ratu (Universitas Nusa Cendana, 2020)
The performance of conventional banking and sharia banking had a major role for the economy inIndonesia when the global economic crisis was 2008. The crisis that occurred in the United Statesaffected the development of banking performance in Indonesia. The research aims to determine thecomparison of financial performance of Sharia banks and conventional banks before, during, andafter the global economic crisis of 2008. Samples in this study were 3 conventional banks and 3sharia banks. Sampling technique is the purposive sampling method, which the criteria are basedon the banking financial report in the year of 2007-2009. The analytical methods in this study usefinancial ratios and the indicators are Adequacy Ratio (CAR), Return On Assets (ROA), Loan toDeposit Ratio (LDR), Operating Load/Operating Income (BOPO) and Non Performing Loan(NPL). The results of this study showed that conventional banking performance was more effectivethan sharia banking before, during and after the economic crisis of 2008. Keywords: Financial Performance, Conventional Banking, Sharia Banking, Financial Ratios.